Effects of CYP3A4 and P-glycoprotein inhibition or induction on the pharmacokinetics of ubrogepant in healthy adults: Two phase 1, open-label, fixed-sequence, single-center, crossover trials - Abhijeet Jakate; Ramesh Boinpally; Matthew Butler; Wendy Ankrom; Marissa F Dockendorf; Antonia Periclou (SAGE Publishing, 2021)
Background: Ubrogepant is metabolized by cytochrome P450 3A4 (CYP3A4) and is a P-glycoprotein (P-gp) substrate. Objective: To assess effects of multiple-dose moderate-strong CYP3A4 and strong P-gp inhibitors and inducers on ubrogepant pharmacokinetic (PK) parameters. Methods: Two phase 1, open-label, fixed-sequence, single-center, crossover trials enrolled healthy adults to receive ubrogepant 20 mg with/without verapamil 240 mg (a moderate CYP3A4 inhibitor) or ketoconazole 400 mg (a strong CYP3A4 and P-gp transporter inhibitor) (Study A), or ubrogepant 100 mg with/without rifampin 600 mg (a strong CYP3A4 inducer and P-gp inducer) (Study B). Outcomes included ubrogepant PK parameters (area under plasma concentration-time curve, time 0 through infinity [AUC 0-∞ ], peak plasma concentration [C max ]), and safety (treatment-emergent adverse events [TEAEs]). PK parameters were compared between ubrogepant with/without coadministered medications using linear mixed-effects models. C max and AUC 0-∞ least-squares geometric mean ratios (GMR) of ubrogepant with/without coadministration were constructed. Results: Twelve participants enrolled in Study A and 30 in Study B. AUC 0-∞ and C max GMR (90% CI) were 3.53 (3.32-3.75) and 2.80 (2.48-3.15), respectively, for ubrogepant with verapamil; 9.65 (7.27-12.81) and 5.32 (4.19-6.76) with ketoconazole; and 0.22 (0.20-0.24) and 0.31 (0.27-0.36) with rifampin. TEAEs were predominantly mild; no treatment-related serious TEAEs or TEAE-related discontinuations occurred. Conclusion: The PK of ubrogepant were significantly affected by the concomitant use of CYP3A4 moderate-strong inhibitors and strong inducers.